FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN ANDROPAUSE PADA PRIA USIA 30-50 TAHUN (Studi di Kecamatan Pedurungan Kota Semarang) - Syarifah Hidayatullah; Ari Udiyono; Lintang Dian Saraswati; Praba Ginandjar (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Andropause is a state of diminished or absent sperm production and testosterone hormone by the testes of male due to the aging process. The difference in onset of andropause is caused by various factors. In addition to being affected by age that can not be changed. The purpose of this study was to determine the factors associated with the incidence of andropause in men aged 30-50 years. This study uses analytic observational research tye with cross-sectional study design. A total of 106 male respondents aged 30-50 years who meet the criteria of entry as research subjects. The sample is selected using purposive sampling. Based on the results of bivariate analysis with chi square test proved the correlation between age (p<0,001; POR=18,0; 95% CI 6,650-48,721), smoking (p=0,045; POR=2,609; 95% CI 1,107-6,150), blood pressure (p=0,002; POR=1,863; 95% CI 1,545-2,245), and work stress (p=0,009; POR=3,238; 95% CI 1,411-7,432). Meanwhile, between Body Mass Index (BMI), alcohol consumption, physical activity, and fasting blood sugar level is not related to the incidence of andropause. From this research, it can be concluded that the factors that influence of andropause are age, smoking, blood pressure, and work stress.